7. Nilai Pelanggan Terhadap Kepuasan Pelanggan Maskapai Air Asia Pada Penerbangan Domestik di Indonesia - Vidyana Mandrawaty (Sekolah Tinggi Teknologi Kedirgantaraan, 2017)
The research aims to examine the effect of customer value on customer satisfaction Indonesia Air Asia Airlines Domestic Flight SUB-DPS Routes in Terminal Two Juanda Airport Surabaya. The object of this research is the customers of Air Asia Domestic Flight SUB-DPS Route in Juanda Airport Terminal Two Surabaya. This study uses quantitative medote, the independent variable (X) in this study is the customer value and the dependent variable (Y) in this study is customer satisfaction. With a population of 158, the data analysis method used is simple linear regression. Data analysis techniques and hypothesis testing using SPSS V.22 software tools. The results of data processing are obtained that the customer value variable has no significant effect on customer satisfaction indicated by the value of t count of 0.487 <1.981 from t table and a significant value of 0.487b> 0.05 significant probability. So Ha is accepted and H1 is rejected. The effect of customer value on customer satisfaction is shown by R Square of 0.004 (0.4%) so that there is no effect on customer value on customer satisfaction.